Are park availability and satisfaction with neighbourhood parks associated with physical activity and time spent outdoors? - Jenny Veitch; Laura Rodwell; Gavin Abbott; Alison Carver; Elliott Flowers; David Crawford (BMC, 2021)
Abstract Background There is substantial scope for enhancing population health through increased park visits and active use of parks; however, a better understanding of factors that influence park visitation is needed. This cross-sectional study examined how parent-reported satisfaction and perceived availability of parks were associated with adults' physical activity and children's physical activity and time spent outdoors, and whether these associations were mediated by park visitation. Methods Self-reported surveys were completed by adults living within 5 km of two parks located in Melbourne, Australia. Participants reported their satisfaction with neighbourhood park quality, walking duration from home to the nearest park, and park visitation in the past 7 days. Participants with a child aged 2-15 years also answered similar questions in relation to their child. The primary outcome variable for adults was leisure-time physical activity (LTPA) and for children was proxy-reported time spent outside. The secondary outcome for adults was combined transportation and LTPA and for children (5-15 years) was the number of days physical activity recommendations were met in the past 7 days. Results Significant positive associations between park availability and park visitation in the past 7 days, and between park visitation and the outcome variables were observed among both adults (n = 1085, M age  = 48.9, SD 13.4) and children (n = 753, M age  = 8.8, SD = 3.7). The association between park satisfaction and park visitation was only significant among adults. Park visitation mediated associations between park availability and park satisfaction and the outcome variables among both adults and children. Conclusions Improving park availability and users' satisfaction with parks may increase visitation and consequently increase physical activity and time spent outdoors.